MAKNA LAGU DAERAH (SAMBOLO) DALAM NILA-NILAI BUDAYA KEHIDUPAN MASYARAKAT DI DESA KOPIDIL KECAMATAN KABOLA - Marta Simey Famau; Yulistina Hiuw Maro, Noni Wulandewi Maulau, Obetnego Kamalau, Daud Hugo Kafomai, Halena Muna Bekata, (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to determine the meaning of folk songs (Sambolo) in the cultural values of community life in Kopidil Village, Kabola Subdistrict. This research is a qualitative research method with an ethnographic approach. The methods used in this research are interviews and field observations. The results showed that the folk song ‘sambolo’ is one of the cultural heritages that is rich in meaning and values upheld by the Kopidil village community. The sambolo song contains moral messages, ethics, and local wisdom that are still relevant to the lives of Kopidil people today such as (1) Gotong royong and togetherness; (2) Gratitude and love for nature; (3) Respect for parents and ancestors; (4) Hard work and fighting spirit (5) Love and loyalty, courage, and heroism.